Accessibility of third-party transit apps and the role of transit agencies and their open data - Mahtot Gebresselassie; Melanie Baljko (Transportation Research Interdisciplinary Perspectives)
Transit agencies like other municipal and other governments and agencies are increasingly adopting open data agendas, often in the form of policy initiatives. Transit agencies are also subject to legislatively mandated accessibility requirements for their service offerings, for instance in the United States, the Americans with Disabilities Act or Section 508 of the Rehabilitation Act. What happens at the convergence of transit agencies’ open data initiatives and regulatory requirements? In this paper, we examine this question through the lens of transit open data used to develop smartphone apps that are used to navigate the transit agencies’ services. Using a qualitative approach, we investigate the extent of open data usage by third parties, the nature of the relationships between transit agencies and open data users, and, particularly, the extent to which the requirements of disability accessibility compliance are made of open data users by the transit agencies. We find that, despite their inferred relevance, there was no required compliance of accessibility regulations in the open-data products, third-party transit apps, except by one transit agency, highlighting discord at the convergence of open data initiatives and regulatory requirements. The purpose of the study is to create knowledge around the convergence to inform policy making and opportunities for change as transit operators continue to make open data available.